ENSINO DE HISTÓRIA LOCAL E PATRIMÔNIO: O CASO DO SÍTIO HISTÓRICO PORTO DE SÃO MATEUS - Marques, Adilson Bulado (2019)
This research addresses the teaching of local and regional history, specifically analyzes the uses and possibilities that the Porto de São Mateus Historic Site can offer as a source for history research and teaching. Historical accounts and records mention the region of São Mateus since the beginning of Portuguese colonization, and Porto played a central role in regional development and for a long time, the only way to enter the region, since it had no roads. With the decay of port activities and the opening of roads that cut this space, Porto was losing its original function, trade was transferred to the upper city and the old houses transformed into cabarets, and these were closed in the context of the military dictatorship. After its near disappearance, Porto was listed as a historical heritage by the State Department of Culture. However, despite its historical importance, it remains forgotten and marginalized by the local population. As for the teaching of history, it is noteworthy that the municipality has legislation that requires the teaching of local history in schools of the municipal network, and has a greater workload of discipline for teaching local content. However, when analyzing the Teaching Program of the Municipal Secretariat of Education, we realize that it is in disagreement with the new historiographic trends. Thus, we investigate how the teaching of local history in São Mateus happens and the uses of the Porto Historical Site in this process. To this end, we used interviews with the teachers of the history of the municipal school system, which showed distances between the teachers and the referred cultural heritage. In addition, we have reviewed official documents, such as the law governing local history teaching in Sao Mateus, as well as the History Teaching Program. Finally, in the light of Walter Benjamin (1996) and Marc Bloch (2001) with their respective concepts of experience and historical source, we analyze and point out possibilities that the São Mateus Port Historic Site and the discourses about it can offer in favor of a most significant local history.